The Construction and Validation of Scale of Effective Factors in Drug Abuse Tendency among Youth (A Case Study in Khorasan Razavi) - Amin Mohammadi; Abdolvahab Pourghaz; Maedeh S Raghib (Drug Control Headquarters, Research and Education Office, 2013)
Objective: Present study has been conducted to construct and validate a scale for assessing of the effective factors of drug abuse tendency among youth. Method: A descriptive method has been used. In this research 408 addicted young adults aged 16-29 years old selected of addiction treatment centers of Razavi Khorasan province during December 2011 till June 2012 by purposive and sequential sampling. For gathering data, 78 items researcher-made questionnaire was administered among selected sample. Results: The face and content validity of scale were approved by the specialists in psychology and sociology. Also, second-order confirmatory factor analysis was used to estimate the construct validity. Result of the research declared that total structure of scale with its three dimensions namely: personal, interpersonal and environmental and social factors for measuring of effective factors of drug abuse tendency. The reliability coefficient of the scale by using of Cranach's alpha coefficient was 0.94. Conclusion: The results indicated that this scale is a valid and reliable instrument for measuring effective factors of drug abuse tendency among youth and it can be used in the same statistical population.